2008
DOI: 10.1016/j.jmb.2008.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic and Equilibrium Molten Globule Intermediates of Apoleghemoglobin Differ in Structure

Abstract: An important question in protein folding is whether molten globule states formed under equilibrium conditions are good structural models for kinetic folding intermediates. The structures of the kinetic and equilibrium intermediates in the folding of the plant globin apoleghemoglobin have been compared at high resolution by quench-flow pH-pulse labeling and interrupted H/D exchange analyzed in DMSO solvent. Unlike its well-studied homolog, apomyoglobin, where the equilibrium and kinetic intermediates are quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…With the exception of Tyr 114 , these protection factors are low and do not exceed a value of ϳ300 (Table 1). These protection factors are comparable with those observed for the molten globules of apomyoglobin (36), apoleghemoglobin (41), and RNase HI (42). In contrast, backbone amides of native apoflavodoxin have protection factors up to 2 ϫ 10 6 .…”
Section: Volume 285 • Number 6 • February 5 2010supporting
confidence: 79%
See 1 more Smart Citation
“…With the exception of Tyr 114 , these protection factors are low and do not exceed a value of ϳ300 (Table 1). These protection factors are comparable with those observed for the molten globules of apomyoglobin (36), apoleghemoglobin (41), and RNase HI (42). In contrast, backbone amides of native apoflavodoxin have protection factors up to 2 ϫ 10 6 .…”
Section: Volume 285 • Number 6 • February 5 2010supporting
confidence: 79%
“…This ordering is due to ␣-helix formation and local and non-local hydrophobic interactions. The ordered regions comprise residues Ala 41 (44). These structured elements in the unfolded protein transiently interact and subsequently form the ordered core of the off-pathway molten globule.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive experiments on apomyoglobin have shown that the hydrogen-exchange protection in the acid state molten globule follows a slightly different pattern and has a different stability distribution than observed in the kinetic intermediate (26,27). In a related protein, apoleghemoglobin, there are substantial structural differences between the protection in the acid state molten globule and the kinetic intermediate (28). Though conformational heterogeneity has been observed in the kinetic intermediate of apomyoglobin, such observations are not incompatible with a region of structure that remains well folded (25,27,29).…”
Section: Discussionmentioning
confidence: 99%
“…Structural characterization of intermediates or MG state that populate in the folding/unfolding process is essential to understand the protein folding mechanism [4]. At MG state, the protein retains most of the secondary structures, but has a tendency to lose some of the tertiary structures [5][6][7]. The MG states are believed to be general folding intermediates because they populate both in the equilibrium and kinetic folding/ unfolding pathways [8].…”
Section: Introductionmentioning
confidence: 99%